Mothers who kill - Beyer, Charlotte, 1965-; Savarese, Josephine, 1962- (Demeter Press, 2021)
This compelling and unique collection of critical and creative work assesses for the first time cultural, literary, legal and historical representations and narratives about mothers who kill and filicide. The idea of a mother killing her child to many presents the greatest taboo, and the most disturbing and distressing aspect of maternal experience. In Toni Morrison's 1987 novel Beloved, escaped slave mother Sethe addresses her daughter Beloved whom she murdered out of desperation, in order to avoid her returning to a life of slavery and sexual abuse. Sethe reflects, ""I'll explain to her, eve.